Directed C–C bond cleavage of a cyclopropane intermediate generated from N-tosylhydrazones and stable enaminones: expedient synthesis of functionalized 1, 4-ketoaldehydes. Issue 91 (2nd November 2017) - Ni, Meiyan; Zhang, Jianguo; Liang, Xiaoyu; Jiang, Yaojia; Loh, Teck-Peng
Abstract : An efficient method to construct functionalized 1, 4-ketoaldehydes bearing all-carbon α-quaternary centers via regioselective C–C bond activation has been described. Abstract : An efficient method to construct functionalized 1, 4-ketoaldehydes bearing all-carbon α-quaternary centers via regioselective C–C bond activation has been described. The cyclopropanation of bench-stable enaminones with in situ generated diazo reagents from N -tosylhydrazones, followed by selective C–C bond cleavage of the cyclopropane ring, affords 1, 4-ketoaldehyde derivatives in good to excellent yields. This method works with broad substrate scope and high regioselectivity.